Study on the boundary layer wind tunnel testing procedure for low-rise scale model buildings - De Lara, Dominique Pocholo P.
In preparation for the acquisition of a Boundary Layer Wind Tunnel in UP Diliman, there is a need to prepare a guideline or procedure for wind tunnel testing. The purpose of this study is to prepare and demonstrate procedure for wind tunnel testing of low-rise scale model buildings. Since the wind tunnel is yet to be procured, the study will focus on the determination of the model length scale, determination of appropriate sampling parameters, identification of guidelines for modeling of the atmospheric boundary layer, development of a calibration set-up and procedure in applying appropriate correction due to tubing system, and post-processing procedures of pressure coefficients. For the scaling, the wind velocity profile and wind turbulence parameters will be utilized. The measured pressures will be corrected by applying the transfer function obtained from the calibration apparatus. For the pressure coefficients, aerodynamic theories and statistical techniques will be applied. At the end of this study, a guideline in model scaling, pressure correction and post-processing is expected as output.